Follow Your Conscience? A Comparison of Aquinas and Arendt - Heribertus Dwi Kristanto; Arokiaraj Joseph Patrick (Jurnal Filsafat "WISDOM", 2026)
Should we always follow our conscience? Through a close reading of the works of Aquinas and Arendt, this paper argues that conscience alone is insufficient for determining right actions. After witnessing Eichmann’s trial, Arendt questioned the reliability of conscience as traditionally understood. Traditionally, conscience is considered the voice of God and an infallible moral compass. Aquinas, a traditional thinker, developed a systematic theory of conscience. However, Aquinas does not view conscience as the voice of God or an infallible moral guide. Rather, conscience is an act of reason applying moral knowledge to particular actions. Consequently, conscience is fallible and must be supplemented by moral virtues and prudence (prudentia). Prudence is the practical wisdom that guides the will and helps one discern the best course of action in specific circumstances. For Arendt, conscience is a byproduct of thinking that evaluates one’s actions. Since thinking is an inner dialogue, conscience is subjective and requires judgment—namely, the capacity to evaluate actions from others’ viewpoints through mutual debate and enlightenment. In conclusion, prima facie, we must always listen to the voice of our conscience, but not without critical reflection and prudence.